HUBUNGAN PENGETAHUAN DAN PARITAS IBU HAMIL DENGAN KEJADIAN AIR KETUBAN KERUH (AKK) DI KLINIK BIDAN MANDIRI HIRAWATI, S.Keb DESA SIMPANG BALIK KECAMATAN WIH PESAM BENER MERIAH: HUBUNGAN PENGETAHUAN DAN PARITAS IBU HAMIL DENGAN KEJADIAN AIR KETUBAN KERUH (AKK) DI KLINIK BIDAN MANDIRI HIRAWATI, S.Keb DESA SIMPANG BALIK KECAMATAN WIH PESAM BENER MERIAH - Nurlaely HS; Levitasari (Jurnal Ilmiah Cerebral Medika, 2022)
ABSTRACT Turbid amniotic water is amniotic water which is turbid yellow and green where the normal amniotic water color is clear and there is a fetal caseosa ferniks exposed to turbid amniotic water at high risk of infection than non-cloudy amniotic water. This study aims to analyze the relationship between the knowledge and parity of pregnant women with the incidence of turbid amniotic water. The type of research used is quantitative research with a Cross sectional approach. The population is 66 pregnant women. The sampling technique is a total sampling with a total sample of 66 respondents. Data collection using questionnaire sheets provided to respondents during a visit to the clinic. Data analysis using the Chi-square test. The results obtained are that there is no relationship between parity and turbid amniotic water with a p value > (0.05) where 0.773 > 0.05. There is no relationship between knowledge and turbid amniotic water and p value > (0.05) where 0.838 > 0.05. Key words: Turbid Amniotic Water ; Parity ; Age ; Knowledge